Sinergi Peran Pemerintah dan Masyarakat dalam Mitigasi Bencana Model Jepang dan Destana Aceh - Farhan Wahyudi; Nabila De Ketty; Mahara Putra Gawa; Maryam; Nurul Kamaly (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
Regional vulnerability caused by geographical conditions to geological and hydrometeorological disasters requires an effective and integrated mitigation model. Japan is widely recognized as a reference due to its ability to integrate policy systems, technology, and the disaster preparedness culture known as Bousai. In contrast, This study employs a qualitative approach using a Systematic Literature Review method. Data were collected from 25 selected publications published between 2010 and 2025, including international and national scientific journals, Japanese disaster management white papers, and official reports from BNPB and BPBA. Data analysis was conducted using constant comparative analysis to identify patterns of government and community synergy in both models.The findings reveal three main results. First, Japan’s disaster mitigation system is highly institutionalized through the Kyojo mechanism, supported by strong regulations and structured access to resources. Second, Destana in Aceh relies on social capital and local values, yet its implementation is constrained by coordination issues and program sustainability challenges. Third, the effectiveness of synergy is determined by the level of integration between formal policies and community-based practices.This study highlights that disaster mitigation effectiveness is not solely determined by policy strength, but also by the degree of alignment between state systems and community capacity. The integration of Japan’s structural approach and Aceh’s social-based approach emphasizes the importance of adaptive mitigation models suited.